OBTENÇÃO DE COMPOSIÇÕES CERÂMICAS Mn-Ni-Co VIA SÍNTESE POR LIOFILIZAÇÃO E SUA CARACTERIZAÇÃO ELÉTRICA COMO SENSOR DE TEMPERATURA. - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
This work describes the preparation of nanoparticles of spinel structure, made from oxides of Manganese, Nickel and Cobalt, via lyophilization process, which was compared to the process of obtaining conventional mixture of oxides, in order to analyze different forms of preparation and its influence on electrical properties (characteristic resistance, temperature coefficient, stability of the thermistor), through the measures obtained by applying a voltage of 5 volts on pads and subjecting them to a temperature range of 20 C to 300 C, measured with a thermocouple type K The microstructures were analyzed by scanning electron microscopy (SEM), the average particle size ranged from 60 to 93 nm. X-ray spectroscopy to determine the phases present in the samples and analysis of infrared to identify in the process, organic waste and the organic phase transitions were completely volatilized during the controlled heating pad on high-temperature furnace (with resistance molybdenum silicide) (Lindenberg). Through the obtained results it was noted a certain advantage at all temperatures of the samples had the composition Ni Mn and Co on the Mn Ni which had only giving larger values between 4335 and 4571 for samples made from the process liofilization.
Keywords: sensores de temperatura; freeze drying; Liofilização, óxidos de Mangânes Niquel e Cobalto; temperature sensors; freeze drying; liofilization; manganese oxides Nickel and Cobalt; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA